Początki polskiego stylu naukowego – między teorią naukową a praktyką gospodarczą - Biniewicz, Jerzy (Stylistyka, 2020)
The author focuses on the history of the Polish scientific style. The Polish scientific style begun to evolve in the sixteenth century. Science is a vehicle for empirical, theoretical, and practical knowledge about the natural world. In the 16th century, many scholars believed that mathematics was the right tool for solving practical problems often faced by craftsmen and merchants. The first Polish texts on mathematics proposed a lecture about the basics of arithmetic and geometry. The author discusses the first scientific texts written in Polish, namely Algorithmus: To jest nauka Liczby: Polsk¹ rzecz¹ wydana (1538) (Algorithmus: This is the Science of Numbers: Published in the Polish Language) by Tomasz K³os, Algorytm (1553) (Algorithmus) by Bernard Wojewódka and Geometria, To jest Miernicka Nauka, po polsku krótko napisana z greckich i z ³aciñskich (Geometry, This is the science of Land Surveyors, briefly in the Polish Language written from Greek and Latin Books) (1566) by Stanis³aw Grzepski. The analysis of the language of science formation in the 16th century Poland shows that already in the early phase of its creation certain properties that characterize Polish modern academic discourse can be seen, namely bilingual communication, preference for specialist language, a rhetorical figure and the use of specific forms of the verb.